The Transformative Impact of Cloud Computing on Tertiary Education (American Journal of Smart Technology and Solutions, 2024)
This systematic literature review investigates the transformative impact of cloud computing on tertiary education by synthesizing findings from 30 scholarly journals and publications across diverse databases. Higher education is beginning to be significantly shaped by cloud computing because education is becoming increasingly electronically integrated. The study uses a thorough and exacting methodology to locate pertinent publications in databases including IEEE Xplore, PubMed, and ScienceDirect using methodical search techniques. The analysis spans a range of publication years to capture the evolution of cloud computing in tertiary education, examining the dynamic interplay between technological advancements and pedagogical practices. The review explores critical themes, including the scalability of cloud solutions, enhanced collaboration and communication tools, and the impact on student learning outcomes. Additionally, the methodology includes a qualitative assessment of the identified literature, critically evaluating the methods employed in the primary studies. This synthesis provides valuable insights into the multifaceted ways in which cloud computing is transforming tertiary education. By delving into the methodologies of the selected studies, the review offers a comprehensive overview of existing knowledge and contributes to the methodological discourse in the field. Ultimately, this research enhances our understanding of the transformative potential of cloud computing in shaping the future of higher education.